Fading frontiers? : a historical-theological investigation into the notion of the 'elementa ecclesiae' - Arenas, Sandra (Bibliotheca Ephemeridum theologicarum Lovaniensium, 2021)
"One aspect of the ecclesiological renewal at Vatican II that has not received much scholarly attention so far is the doctrine of the "elements of the church" (elementa ecclesiae), previously unheard of in Roman Catholic magisterial documents. This book offers an original and comprehensive study of this notion and how it became part of the official teaching of the Roman Catholic church. Using a historical-theological approach, the author studies the origins and evolution of the concept of the "elements of the church" and gives a nuanced understanding of this doctrine as outlined in Lumen gentium [section] 8 and Unitatis redintegratio [section] 3. In this way, the author offers a renewed insight into the evolution of the position of the Roman Catholic church "in oecumenicis" during and in the aftermath of Vatican II. The development sketched in the book is characterized by a double perspective. On the one hand, there is the debate about the frontiers of the church that focuses on the relationship between the Roman Catholic church and the church of Christ. On the other hand, and closely related to the first aspect, there is the issue of the recognition of "ecclesial" elements in non-Catholic Christian communities. Both threads are closely interwoven and it is important to understand the relationship if one wants to do justice to the doctrinal balance and complexity of Vatican II's ecumenical ecclesiology." --